Habronematidosis in Equids: Current Status, Advances, Future Challenges - Barlaam, Alessandra; Traversa, Donato; Papini, Roberto; Giangaspero, Annunziata (Frontiers in Veterinary Science, 2020)
Over the past few decades, among equine parasitoses caused by gastrointestinal nematodes, habronematidosis has been discontinuously studied worldwide. Habronematidosis is a parasitic disease distributed all over the world. It is caused by Habronema microstoma, Habronema muscae, and Draschia megastoma (Spirurida, Habronematidae), and it is maintained in the environment by muscid flies which act as intermediate hosts. At larval and adult stages these species live in the stomach of domestic and wild equids. However, the larvae can also be found on the skin, causing lesions known as “summer sores”, and occasionally on other body areas, such as ocular and genital mucosa (muco-cutaneous habronematidosis) and lung, liver, brain parenchyma. Depending on the parasite's developmental stage and localization site, clinical signs vary from mild to severe. Habronematidosis is responsible for significant economic losses, mostly when sport horses are affected, because their performances are impaired and the infection can be unaesthetic. We used three on-line databases for searching the articles on habronematidosis according to the selected inclusion criteria; a total of 250 contributions, published between 1911 and 2020 were analyzed. This review summarizes the key features of pathogenesis, epizootiology, diagnosis, treatment, and control of habronematidosis, and highlights the current knownledge about its geographical distribution and spread. Anthelmintic drugs are the most widely-used tools against habronematidosis; given the known risk of anthelmintic resistance in some nematodes affecting horses, this aspect should also be explored for habronematidosis. Dedicated research is essential to fill gaps of knowledge and increase the understanding of habronematidosis to maximize equine health, reduce economic losses and sanitary impact associated with this parasitic infection.